Al-Tadrībāt al-Lughawiyyah al-Mushawwiqah fī Taʿlīm al-Lughah al-ʿArabiyyah ʿalā Ḍawʾ Mahārat al-Kitābah - yoke suryadharma (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2016)
Language exercises are among the most essential means of developing language proficiency, as language learning fundamentally requires continuous practice and repeated training. As commonly expressed in English, "language must be practiced," effective language acquisition depends on regular and sustained application. Linguists likewise emphasize that learners can only achieve linguistic competence through consistent practice and ongoing exercises. Therefore, Arabic language teachers need to employ engaging and effective instructional exercises to enhance students' learning experiences. This article discusses the fundamental principles of language exercises in Arabic language teaching, the formulation of engaging language activities, and their various types within the context of writing skills. It presents eighteen comprehensive exercise models designed to promote writing proficiency, each incorporating innovative and creative approaches to answering questions.